Am I My Brother's Keeper? The Jewish Committees in the Ghettos of Mogilev Province and the Romanian Regime in Transnistria during the Holocaust, 1941–1944†. Issue 2 (3rd May 2016) - Tibon, Gali
Abstract : This paper deals with the unique conduct of the Jewish Committees in the Mogilev District ghettos in Transnistria in saving their community members and coping with the Romanian authorities between 1941 and 1944. As the Holocaust raged throughout Europe and the Soviet Union, the Jews from Bessarabia, Bukovina and Dorohoi were expelled from Romania and arrived gradually in Mogilev province in the summer and autumn of 1941. A total of 195, 000 Jews were deported from these regions to Transnistria, and only about 45, 000 returned to Romania at the end of the war. The deportation to Transnistria emphasized the differences between wealthy and needy families among the Jews, and between the communities from south Bukovina and those from north Bukovina and Bessarabia. At the heart of the conflict were the Jewish Committees' actions: the expulsion of thousands of Jews from the Mogilev District ghettos to the starvation death camps of Scazinsti and Pechora in July and again in October 1942.